2016
DOI: 10.4172/2165-7556.1000176
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carrying Loads on Ratings of Perceived Exertion and Heart Rate during Walking

Abstract: Introduction: There is evidence that schoolbags may be a contributing factor for musculoskeletal complaints in schoolchildren. Several studies have reported an association between carrying heavily loaded schoolbags and musculoskeletal pain or discomfort. Methods: 105 collegiate students were conveniently recruited in this study; heart rate (HR) and perceived exertion were measured immediately after the treadmill walking with the back pack, right side pack and left side pack. Subject has to walk for 20 min afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…[9] Children between the age group of 13-16 years are of great concern as junior students in secondary school have a critical spinal development stage. [3] Osgood-Schlatter syndromeone of the most common orthopedic diseases can be related by heavy loading on the patellar tendon leading to tendinopathy. Adding load can further worsen the condition for these school going children.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Children between the age group of 13-16 years are of great concern as junior students in secondary school have a critical spinal development stage. [3] Osgood-Schlatter syndromeone of the most common orthopedic diseases can be related by heavy loading on the patellar tendon leading to tendinopathy. Adding load can further worsen the condition for these school going children.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they concluded that females should carry load less than 10% of BW, whereas, men can carry up to 15% static load of BW for the time period of 15 minutes. [2] reported the relation between musculoskeletal pains or discomforts associated with heavily loaded school bags. A treadmill test was conducted on 105 students walking with different loads such as right side, left side, and back loads, respectively.…”
mentioning
confidence: 99%